Recent Status of Covid-19 Pandemic: A Perspective to Global and Indian Scenario - George, John; Paulson, Sandra (Recent Developments in Medicine and Medical Research Vol. 15, 2021)
This article seeks to narrate the origins of the Covid-19 infection from patient zero and the spread of the disease into a destructive pandemic. Analyzing how the world came together to try bringing the disease under control in a coordinated manner till date. The authors wish to convey to the public the unfolding of the disease and the developments thereafter in a simple and straightforward manner.